2022
DOI: 10.1101/2022.01.28.22270039
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ready for Impact? A validity and feasibility study of instrumented mouthguards (iMGs)

Abstract: Objectives Determine the validity and feasibility of current Instrumented mouthguards (iMGs) and associated systems. Methods Phase 1; Four iMG systems (Football Research Inc [FRI], HitIQ, ORB, Prevent) were compared against dummy headform laboratory criterion standards (25, 50, 75, 100 g). Phase 2; Four iMG systems were evaluated for on-field validity of iMG-triggered events against video-verification to determine true-positives, false-positives and false-negatives (20 SD 9 player matches per iMG). Phase 3; Fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The measured raw and filtered iMG acceleration timeseries data had total CCC values of 90.7% and 96.7% respectively, when compared to the ATD reference measurement system, and would have met the threshold of 80% or greater to meet a threshold for application to measure on field kinematics [19]. For total CCC values this study found the results of the filtered iMG of 97% to be similar, to the CCC values reported by Jones et al, [18] which investigated the validity and feasibility of a number of different iMG systems.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The measured raw and filtered iMG acceleration timeseries data had total CCC values of 90.7% and 96.7% respectively, when compared to the ATD reference measurement system, and would have met the threshold of 80% or greater to meet a threshold for application to measure on field kinematics [19]. For total CCC values this study found the results of the filtered iMG of 97% to be similar, to the CCC values reported by Jones et al, [18] which investigated the validity and feasibility of a number of different iMG systems.…”
Section: Discussionsupporting
confidence: 80%
“…With the need to accurately utilise new technology to help understand issues within sport such as concussion by measuring head impacts and more importantly using that data to understand brain deformation of the athletes in question. There is a need for a standardised testing and data handling process to ensure that the observed results are comparable and that a suitable decision can be made by researchers and practitioners about what measurement device is appropriate to use [18]. Therefore, future studies should incorporate standardised data processing techniques when validating and comparing iMG systems or using iMG systems to measure head impact accelerations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations